2019
DOI: 10.1039/c8cc08856j
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically driven interfacial halogen bonding on self-assembled monolayers for anion detection

Abstract: The concept of anion detection via reversible electrochemically driven charge-assisted halogen bonding in solution was transferred on the surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 53 publications
2
37
0
Order By: Relevance
“…5,6 This has also been exploited in electrochemical anion sensors in solution, [7][8][9][10][11] and, very recently, at receptive interfaces. [12][13][14] The surface-immobilisation of (redox-active) receptors is relevant to the development of real-life relevant sensors, [15][16][17][18] enabling facile sensor reuse, and sensing both under flow and in (aqueous) solvent media in which many synthetic receptors are not natively soluble. 1,19 Our quantitative understanding of anion sensing at redox-active interfaces, does, however, remain underdeveloped.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 This has also been exploited in electrochemical anion sensors in solution, [7][8][9][10][11] and, very recently, at receptive interfaces. [12][13][14] The surface-immobilisation of (redox-active) receptors is relevant to the development of real-life relevant sensors, [15][16][17][18] enabling facile sensor reuse, and sensing both under flow and in (aqueous) solvent media in which many synthetic receptors are not natively soluble. 1,19 Our quantitative understanding of anion sensing at redox-active interfaces, does, however, remain underdeveloped.…”
Section: Introductionmentioning
confidence: 99%
“…1,19 Our quantitative understanding of anion sensing at redox-active interfaces, does, however, remain underdeveloped. 14,18,[20][21][22] Often an enhanced sensory performance (larger signal magnitude) is observed on confining redox-active receptors to interfaces, 19, 23 but the specific physico-chemical origins of this remain poorly understood. It has been suggested that an enhanced interfacial binding strength, brought about by receptor preorganisation and/or cooperative/chelate effects is the origin of the surface-enhancement effect.…”
Section: -14mentioning
confidence: 99%
“…15, 20, 34 Although this has been attributed to surface confined receptor preorganisation and/or cooperative/chelate binding, this does not fully explain the observations herein. 14,15,20 Receptor immobilisation within compact films will reduce any entropic penalty associated with anion binding, but other factors, including receptor and anion dehydration, are likely to be important. More importantly, the magnitude of the voltammetric response is determined by the BEF and not the absolute magnitude of the binding (to any one receptor oxidation state).…”
Section: Comparison Of Diffusive and Surface-confined Sensor Responsementioning
confidence: 99%
“…These relatives of the HB are hardly exotic academic novelties, but have a wide range of applications, such as serving as synthons in self-assembling networks [117], biological catalysis [118], oxidative addition [119], self-assembled monolayers [120], SN2 reaction catalysis [121], design of functional mesomorphic materials [122], and even directed construction of supramolecular quadruple and double helices [123]. One of the more interesting uses concerns selective binding of anions [124][125][126][127][128][129][130][131].…”
Section: Cousins Of Hbsmentioning
confidence: 99%